Relationship of socioeconomic factors with vision-related quality of life on severe low vision and blind population in Indonesia (Faculty of Medicine Universitas Indonesia, 2015)
Background: Socioeconomic factors are known to be associated with visual impairment. Being someone who is visually impaired could affect his quality of life. The aim of this study is to evaluate the quality of life (QOL) in severe low vision and blind population in Indonesia in relation to their socioeconomic status. Methods: A cross sectional population-based study was performed in 5 provinces, in Indonesia. Respondents of validation study on blindness data of national basic health survey 2013 (RISKESDAS 2013), who were above 18 years old with severe low vision (BCVA≥3/60 to 6/60) and blind (BCVA<3/60), were included in this study. Questionnaires for socioeconomic status and a questionnaire from the national eye institute visual function questionnaire 25 (NEI VFQ 25) for visual function were administered. Total scores of NEI-VFQ25 were compared based on severity of visual impairment, educational level, occupation, literacy adequacy, income level, and residency. Data analysis was using independent T-test or Mann-Whitney test, and Chi square test. Results: A total of 134 subjects were enrolled in this study, most of them are women (68.2%), aged >64 years old (64.9%) with low education (65.7%), illiterate (52.2%), low income (71.6%), non working (63.4%) and living in urban areas (58.2%). The blind population has lower VFQ scores than severe low vision (p=0.001). Different status of educational level, literacy adequacy, income level and residency did not show significant difference in VFQ scores, but those who have an occupation had better VFQ scores than those who do not (p=0.041). Conclusion: Visual related quality of life (VRQOL) of severe low vision and blind population was associated significantly with occupational status. Because of culture and characteristics of Indonesian people, VRQOL of severe low vision and blind population in Indonesia was not affected by educational level, literacy, income level, and residency.